Study of the Sustainable Livelihood Framework on the Implementation of the Agrarian Reform Program (Case Study: Pasaman Regency) - Sisilia, Debbi; Suhirman, Suhirman (The Indonesian Journal of Planning and Development, 2023)
Poverty and employment are socio-economic issues that are often a problem in Indonesia, including in the West Sumatra. The high poverty and unemployment rates in West Sumatra cause its people trying to make use of their capital to survive. One of the basic components utilized by the community is the availability of land. However, the level of inequality in the distribution of land tenure and ownership is quite high. To solve these problems, government development the Agrarian Reform Program. One of the locations of the agrarian program is Pasaman Regency. The use of land as an effort to support people's livelihoods depends on the livelihood strategies and influences livelihood outcomes. The livelihood outcome depends on external and internal factors that are inherent in people's livelihoods, as stated in the Sustainable Livelihood Framework (SLF). This research uses the SLF method because the SLF can be used to sharpen the monitoring and evaluation system in development projects. Since 2019, this activity had never been evaluated and it is not yet known how it will impact the community's sustainable livelihoods. Therefore, this study aims to examine the factors that influence the impact of the implementation of the agrarian reform program on the livelihoods of the people in Pasaman Regency. The research results show that the agrarian reform program provides livelihood outcomes in the form of increased welfare, increased income and reduced community vulnerability. This livelihood achievement is influenced by the community's ability to manage livelihood capital, the level of vulnaberality and the transformation of structures and processes to support the community's sustainable livelihoods.